KUALITAS INFORMASI AKUNTANSI, KONEKSI POLITIK DAN EFISIENSI INVESTASI - Ulfah Tika Saputri (Universitas Teknokrat Indonesia, 2021)
Abstract Agency conflict is the root of the problem that causes investment inefficiency. This Research aim to provide that accounting information quality and political connection influence to investment efficiency. We used 70 samples from 100 Company on Compas Index 2019. We used classical assumption test, we used F test, coefficient determination test and partial test. We provide that company on 100 Compas Index mostly have investment inefficient and it can be reduced with high accounting information quality. But, Indonesian company characteristics that they have political connection, even just 45% company has political connection, but political connection makes inefficient. Keyword: Accounting Information Quality: Political Connection: Investment Efficiency